Neutrophil-to-lymphocyte ratio in sporadic amyotrophic lateral sclerosis - Qian-Qian Wei; Yan-Bing Hou; Ling-Yu Zhang; Ru-Wei Ou; Bei Cao; Yong-Ping Chen; Hui-Fang Shang (Neural Regeneration Research, 2022)
The neutrophil-to-lymphocyte ratio (NLR) is considered a robust prognostic biomarker for predicting patient survival outcomes in many diseases. However, it remains unclear whether it can be used as a biomarker for amyotrophic lateral sclerosis (ALS). To correlate NLR with disease progression and survival in sporadic ALS, 1030 patients with ALS between January 2012 and December 2018 were included in this study. These patients were assigned into three groups according to their NLR values: Group 1 (NLR < 2, n = 544 [52.8%]), Group 2 (NLR = 2–3, n = 314 [30.5%]), and Group 3 (NLR > 3, n = 172 [16.7%]). All patients were followed up until April 2020. Patients in Group 3 had a significantly older onset age, a lower score on the Revised ALS Functional Rating Scale, and rapidly progressing disease conditions. Furthermore, faster disease progression rates were associated with higher NLR values (odds ratio = 1.211, 95% confidence interval [CI]: 1.090–1.346, P < 0.001) after adjusting for other risk factors. Compared with Groups 1 and 2, the survival time in Group 3 was significantly shorter (log-rank P = 0.002). The NLR value was considered an independent parameter for the prediction of survival in ALS patients after normalizing for all other potential parameters (hazard ratio [HR] = 1.079, 95% CI: 1.016–1.146, P = 0.014). The effects on ALS survival remained significant when adjusted for treatment (HR = 1.074, 95% CI: 1.012–1.141, Ptrend = 0.019) or when considering the stratified NLR value (HR = 1.115, 95% CI: 1.009–1.232, Ptrend = 0.033). Thus, the NLR may help to predict the rate of disease progression and survival in patients with sporadic ALS. The study was approved by the Institutional Ethics Committee of West China Hospital of Sichuan University, China (approval No. 2015 (236)) on December 23, 2015.